Transformation of Islamic Accounting in Supporting Infrastructure and Regional Economic Development: Transformasi Akuntansi Syariah dalam Mendukung Pembangunan Infrastruktur dan Ekonomi Daerah - Abdul Rahman Ramadhan (PT Syamilah Literasi Islami, 2024)
This research aims to analyze the transformative role of Islamic accounting in supporting infrastructure development and economic growth in various regions in Indonesia. This research discusses the positive impacts of implementing Islamic accounting, including fairness in benefit distribution, sustainable infrastructure development, access to Islamic financing, investor confidence, and conformity with local values. However, it also described constraints such as lack of understanding, limited human resources, regulatory complexity, limited Islamic financial instruments, policy changes, complexity of financial structures, social and cultural changes, and protection against possible misuse. Collaboration between local governments, the private sector, and universities is key to overcoming these obstacles and strengthening the role of Islamic accounting in supporting sustainable regional economic growth and in accordance with sharia values upheld by the Indonesian people. This research is included in the qualitative research method. The data collection technique used in this research is a literature study from secondary data sources in the form of books, journals, scientific articles, official websites that have information relevant to the research topic such as Islamic accounting and economics. The data analysis technique used in this research is content analysis technique to then draw conclusions with deductive method. The results of this research are expected to provide an understanding of the role and potential of Islamic accounting transformation in supporting infrastructure development and economic growth in various regions. as well as identifying the positive potential of the application of Islamic accounting in regional development and revealing the obstacles and barriers that may be faced in applying Islamic accounting in the context of regional infrastructure and economic development.